Quality of life and coping in Dutch homozygous familial hypercholesterolemia patients: A qualitative study. (May 2022) - Mulder, Janneke W.C.M.; Kranenburg, Leonieke W.; Treling, Willemijn J.; Hovingh, G. Kees; Rutten, Joost H.W.; Busschbach, Jan J.; Roeters van Lennep, Jeanine E.
Abstract: Background and aims: Homozygous familial hypercholesterolemia (HoFH) is characterized by severely elevated low-density lipoprotein cholesterol (LDL-C) levels leading to extremely premature atherosclerotic cardiovascular disease. Therefore, healthcare professionals consider HoFH to have major impact on patients' life. Remarkably, little is known on how patients deal with their condition. The aim of this study is to investigate how Dutch patients experience and cope with HoFH in daily life. Methods: Adult patients with genetically confirmed HoFH, treated at the 3 specialized HoFH-centers in the Netherlands, were interviewed in-depth. Interview transcripts were analyzed according to grounded theory. Health-related quality of life (QoL) and coping were measured with the EuroQol (EQ)-5D-5L questionnaire and the Threatening Medical Situations Inventory (TMSI), respectively. Results: 20 Dutch HoFH patients were interviewed: 50% women, median age 38 years, 60% with cardiovascular disease, 10% on apheresis. Coding of the transcripts resulted in a conceptual model, with disease perception as the central theme. Individual TMSI-results corresponded to the interviews, with most patients showing both monitoring (information-seeking behavior) and blunting (distractive strategies) coping styles. The median EQ-5D-5L health utility score (0.839) was only 5% below the Dutch population (0.887). Transient anxiety was reported when confronted with the consequences of HoFH in daily life. Patients reported high confidence in treatment by a dedicated HoFH center, which helped them cope with their disease. Conclusions: Dutch HoFH patients use a variety of effective coping mechanisms in such a way that their subjective QoL is only slightly affected. Healthcare professionals can use this knowledge to tailor their care to the specific needs of these patients. Graphical abstract: Image 1 Highlights: Homozygous familial hypercholesterolemia (HoFH) is considered a serious disorder by healthcare professionals. Little is known about how HoFH-patients cope with their condition in daily life. Quality of life in Dutch HoFH-patients is only 5% lower compared to the general population. Patients use a variety of effective coping mechanisms to deal with HoFH in daily life. Knowledge about coping can help healthcare professionals tailor their care to the specific needs of HoFH-patients.